+0  
 
0
22
1
avatar+180 

Solve for $x$: \(\dfrac{66-2^x}{2^x+3}=\dfrac{4-2^x}{2^{x+1}+6}\)

 
michaelcai  Sep 17, 2017
social bar
Sort: 

1+0 Answers

 #1
avatar
0

Solve for x over the real numbers:
(66 - 2^x)/(2^x + 3) = (4 - 2^x)/(2^(x + 1) + 6)

Hint: | Expand out terms of the left hand side.
(66 - 2^x)/(2^x + 3) = 66/(2^x + 3) - 2^x/(2^x + 3):
66/(2^x + 3) - 2^x/(2^x + 3) = (4 - 2^x)/(2^(x + 1) + 6)

Hint: | Look for an expression to multiply both sides by in order to clear fractions.
Multiply both sides by 2^(x + 1) + 6:
132 - 2^(x + 1) = 4 - 2^x

Hint: | Move everything to the left hand side.
Subtract 4 - 2^x from both sides:
128 + 2^x - 2^(x + 1) = 0

Hint: | Simplify 128 + 2^x - 2^(x + 1) = 0 by making a substitution.
Simplify and substitute y = 2^x.
128 + 2^x - 2^(x + 1) = 128 - 2^x
 = 128 - y:
128 - y = 0

Hint: | Divide both sides by the sign of the leading coefficient of 128 - y.
Multiply both sides by -1:
y - 128 = 0

Hint: | Solve for y.
Add 128 to both sides:
y = 128

Hint: | Perform back substitution on y = 128.
Substitute back for y = 2^x:
2^x = 128

Hint: | Perform the prime factorization of the right hand side.
128 = 2^7:
2^x = 2^7

Hint: | Equate exponents.
Equate exponents of 2 on both sides:
x = 7

 
Guest Sep 17, 2017

25 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details